Challenges for Improved Production and Value Share Along the Honey Value Chain in Ethiopia - Mulubrihan Bayissa; Ludwig Lauwers; Fikadu Mitiku; Dirk C. de Graaf; Wim Verbeke (Agriculture, 2025)
Although Ethiopia has an enormous agroecological potential for beekeeping, only 10% of it is realized. As its conventional smallholder production calls for improvement in market relationships, this paper aims at an in-depth analysis of the honey value chain, value share distribution, and leverages for improvement. Questionnaires, focus group discussions, and key informant interviews were used to collect data. Descriptive statistics, value chain mapping, and margin analysis were used for analysis. The main honey value chain actors were input suppliers, producers (beekeepers), collectors, wholesalers, processors, cooperatives, unions, retailers, and consumers. Agricultural offices, research centers, trade and market development offices, financial institutions, and NGOs are major supporters. The value share of beekeepers using traditional hives is still low, while the largest share goes to improved hive users and wholesalers, respectively. Weak market linkages, high costs and shortage of modern equipment, limited access to credit, lack of legal frameworks and standardized laboratories, absconding, pest infestation, and unsafe use of agrochemicals were the major challenges. Nevertheless, attractive investment policy, global market demand, low capital requirements, and support from NGOs were key opportunities. Improving access to better market, finance and modern inputs, capacity building, legal reform, and a standardized laboratory would help to support the honey value chain and its contribution.